2007
DOI: 10.1093/ajcn/86.3.858s
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin in relation to malignancies: a review of existing basic research and clinical evidence

Abstract: Adiponectin, an adipocyte-secreted hormone that plays an important role in diabetes and cardiovascular disease, may also be of importance in the development and progression of several malignancies. Circulating adiponectin concentrations, which are determined mainly by genetic factors, nutrition, and adiposity, are lower in patients with breast, endometrial, prostate, and colon cancer. It has thus been proposed that adiponectin may be a biological link between obesity (especially central obesity) and increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
255
1
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 318 publications
(270 citation statements)
references
References 111 publications
2
255
1
12
Order By: Relevance
“…Obesity is an established risk factor for various types of cancers (Renehan et al, 2008), and recent studies had shown that adiponectin was a key player in the development and progression of obesity-related cancers (Barb et al, 2007;Paz-Filho et al, 2011). Adiponectin implemented the main biological function through its receptors, which were believed to be also expressed in many types of cancers (Dalamaga et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Obesity is an established risk factor for various types of cancers (Renehan et al, 2008), and recent studies had shown that adiponectin was a key player in the development and progression of obesity-related cancers (Barb et al, 2007;Paz-Filho et al, 2011). Adiponectin implemented the main biological function through its receptors, which were believed to be also expressed in many types of cancers (Dalamaga et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies had revealed that adiponectin, the most abundant adiposetissue protein, was a key player in the development and progression of obesity-related cancers (Barb et al, 2007;Paz-Filho et al, 2011;Liu et al, 2013). Adiponectin is involved in anti-inflammatory, insulin-sensitizing, and anti-proliferation activities which are associated with the development of cancer (Barb et al, 2007;Ziemke and Mantzoros, 2010). Recent studies have confirmed that adiponectin implement the main biological function by signaling through its receptors-ADIPOR 1 and ADIPOR …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The plasma Adipoq concentration is reported to be inversely associated with a variety of human cancers (Barb, 2007), and these findings correlate with the increased risk of cancers in obese people. We therefore also tested whether or not overexpression of Adipoq inhibits tumor growth in an allograft tumor growth model (Yaker, 2006).…”
Section: Introductionmentioning
confidence: 93%